Performances Analysis of a Linear Motor for Sliding Door Application - Aymen Lachheb; Jalel Khediri; Lilia El Amraoui (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The present work deals to investigate the performance of linear switched reluctance motor designed for a sliding door application. The objective of this paper is to develop an analytical model in order to predict the dynamic behaviour of the studied motor. Firstly, the characteristics of the proposed motor in open loop operation was computed.Secondly, the effect of the load on the response of the motor was investigated. In this context, a two technoque in open loop were adopted to solve the error positioning with load and to damp the oscillation observed in the characteristics of the motor in order to obtain a smooth motion.